Mental Health and Well-being training program for volunteers and professionals working with young asylum seekers who live in centers, shelters or refugee camps - Santos, Luisa Micaela Teixeira (2019)
Goals: The project aims to answer the overall research question: What is the feasibility, appropriateness, meaningfulness and effectiveness of Apt4U - Mental health and well-being training program for volunteers and/or professionals working in humanitarian settings with young asylum seekers.